PROGRAM PENGEMBANGAN DESA MITRA DI KIAMA KABUPATEN TALAUD: INSTALASI POMPA AIR TENAGA SURYA - Meita Rumbayan; Sherwin R.U Sompie; Rilya Rumbayan (Institute of Research and Community Outreach - Petra Christian University, 2021)
This community service aims to apply the technology of independence supply electricity based on renewable source of energy that is available locally. This technology is applied in Kiama village that is located in the remote island of Talaud. The problems regarding the limited access of electricity have been faced by the coastal community in Talaud Island. The water pump supplied by solar energy is the most suitable technology to be applied in the area that has limited access to electricity grid. The method of implementing this partner village development program consists of several stages, namely: (1) Application of suitable technology for solar water pump to supply water tank; (2) Transfer technology based on renewable energy utilization to increase knowledge and skills for the community in the remote village. The beneficial aspect of this activity is to improve the knowledge of society toward the renewable energy utilization and to improve of community standard lives toward the access of electricity, independently. The program implementations were designed and built-up of water pump powered by solar energy technology and the one unit installation of the technology to a church in the Kiama village. The results obtained from this activity are improvement of the welfare and the comfort of people's lives due to access to electricity. Regarding appropriate technology applied for the remote communities. Abstrak: Pengabdian kepada masyarakat ini bertujuan untuk menerapkan teknologi kemandirian penyediaan tenaga listrik berbasis sumber energi terbarukan yang tersedia secara lokal. Teknologi ini diterapkan di Desa Kiama yang terletak di pulau terpencil Talaud. Permasalahan keterbatasan akses listrik telah dihadapi oleh masyarakat pesisir di Pulau Talaud. Pompa air yang disuplai tenaga surya merupakan teknologi yang paling cocok diterapkan di daerah yang akses jaringan listriknya terbatas. Metode pelaksanaan program pengembangan desa mitra ini terdiri dari beberapa tahapan, yaitu: (1) Penerapan teknologi tepat guna pompa air tenaga surya untuk mensuplai tangki air; (2) Alih teknologi berbasis pemanfaatan energi terbarukan untuk meningkatkan pengetahuan dan keterampilan masyarakat di desa terpencil. Manfaat kegiatan ini adalah meningkatkan pengetahuan masyarakat terhadap pemanfaatan energi terbarukan dan meningkatkan taraf hidup masyarakat terhadap akses listrik secara mandiri. Implementasi program ini adalah merancang dan membangun pompa air bertenaga teknologi tenaga surya dan pemasangan satu unit teknologi tersebut pada sebuah gereja di desa Kiama. Hasil yang diperoleh dari kegiatan ini adalah peningkatan kesejahteraan dan kenyamanan hidup masyarakat karena akses listrik.